(untitled) (Ustozlar uchun, 2026)
This article provides a comprehensive analysis of the components and communicative functions of intonation in modern English. Intonation is one of the most essential suprasegmental features of spoken language and plays a decisive role in structuring discourse, expressing attitudes, and signaling grammatical relations. The study explores the core components of intonation—pitch, stress, rhythm, tempo, and pause—and evaluates their functional significance across various linguistic contexts. Using descriptive and analytical methods, the research synthesizes theoretical positions of leading phoneticians and compares functional models of intonation. The findings indicate that intonation is a multifunctional system that ensures emotional, pragmatic, and structural coherence in communication.